2023
DOI: 10.1021/acs.bioconjchem.3c00129
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived PD-L1+ Exosomes with Natural Inflammation Tropism for Psoriasis-Targeted Treatment

Abstract: Background: Psoriasis is a chronic and readily recurrent in ammatory skin disease. To date, there is no cure for psoriasis and signi cant challenges remain in developing more safe and e cacious novel targeted therapies. Psoriasis is characterized by abnormal activation of the immune system, and hyperproliferation and aberrant differentiation of keratinocytes. Psoriatic keratinocytes death is also recently recognized as a major ampli er to the initiation of in ammatory cascade. Given that both keratinocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Increased pristimerin uptake with CD4+ T cells and keratinocytes, significantly inhibited the proliferation of Th17 cells, and promoted Treg differentiation in a psoriasis-like model [77] insecticidal --Exhibited marked in vitro leishmanicidal activity against promastigotes [78] Antibiosis --Caused functional alterations on the cytoplasmic membrane of S. epidermidis cells and altered the membrane permeability of S. aureus [79,80] Antiviral Human embryonic fibroblast cell line Inhibited the cytopathic effects in HCMV-infected cells and inhibited the synthesis of viral DNA but had no virucidal effect on cell-free HCMV [81] Anti-osteoporosis Ovariectomy model Inhibited the differentiation and activation of osteoclasts in vitro and in vivo [82][83][84] Ovariectomized rats Caused TRAF-6-deficient transgenic mice to suffer from osteoporosis and exhibit increased osteoclastogenesis mechanism of action of pristimerin is multi-pathway, multi-target and multi-system, which also precisely reflects the advantages of systematization, wide angle and multi-targets of Chinese medicinal preparations in disease treatment. However, there are still many unanswered questions about pristimerin, such as the specific mechanism and target are not clear, the more detailed mechanism is not explored, the common tumor types are not comprehensive, the toxic and side effects are not clear, the clinical application is seriously lacking and the bioavailability is different.In order to achieve success, future studies should focus on the following aspects: (1) to further exploring the specific mechanisms and targets of pristimerin and more detailed mechanisms through network pharmacology, molecular docking.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Increased pristimerin uptake with CD4+ T cells and keratinocytes, significantly inhibited the proliferation of Th17 cells, and promoted Treg differentiation in a psoriasis-like model [77] insecticidal --Exhibited marked in vitro leishmanicidal activity against promastigotes [78] Antibiosis --Caused functional alterations on the cytoplasmic membrane of S. epidermidis cells and altered the membrane permeability of S. aureus [79,80] Antiviral Human embryonic fibroblast cell line Inhibited the cytopathic effects in HCMV-infected cells and inhibited the synthesis of viral DNA but had no virucidal effect on cell-free HCMV [81] Anti-osteoporosis Ovariectomy model Inhibited the differentiation and activation of osteoclasts in vitro and in vivo [82][83][84] Ovariectomized rats Caused TRAF-6-deficient transgenic mice to suffer from osteoporosis and exhibit increased osteoclastogenesis mechanism of action of pristimerin is multi-pathway, multi-target and multi-system, which also precisely reflects the advantages of systematization, wide angle and multi-targets of Chinese medicinal preparations in disease treatment. However, there are still many unanswered questions about pristimerin, such as the specific mechanism and target are not clear, the more detailed mechanism is not explored, the common tumor types are not comprehensive, the toxic and side effects are not clear, the clinical application is seriously lacking and the bioavailability is different.In order to achieve success, future studies should focus on the following aspects: (1) to further exploring the specific mechanisms and targets of pristimerin and more detailed mechanisms through network pharmacology, molecular docking.…”
Section: Discussionmentioning
confidence: 94%
“…75 Pristimerin also inhibits the expression of endothelial adhesion molecules ICAM-1 and VCAM-1 and pro-inflammatory cytokines IL-6, IL-8, and MCP-1 induced by TNF-α-induced inhibition and acts in conjunction with the PD-L1+ exosomes to alleviate the iron-toxicityrelated changes in psoriatic skin, thereby inhibiting excessive inflammation. 76,77 Pristimerin has insecticidal properties, killing Leishmania protozoa and Trypanosoma cruzi and acting as an effective drug for Leishmaniasis and Chagas disease. 78 Pristimerin has antimicrobial properties as well, acting by altering the permeability of the plasma membranes of Staphylococcus epidermidis and Staphylococcus aureus.…”
Section: Antitumor Effects Of Pristimerinmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Jin et al's next-generation sequencing analysis identified specific miRNAs in EpCAM+ exosomes as biomarkers for lung adenocarcinoma and squamous cell carcinoma [68]. In addition to cancer, extensive studies have documented the unique roles of exosomal subpopulations in diseases such as neurodegenerative disorders, liver failure, osteogenesis, and retinal conditions, underscoring the critical function of exosomes in disease pathophysiology and their promise as diagnostic and therapeutic tools [69][70][71][72][73][74][75][76].…”
Section: The Heterogeneity Of Exosome and Biomarker Discoverymentioning
confidence: 99%